Anti-slide pile structure development: New design concept and novel structure - Chen, Guangfu; Guo, Fei; Zhang, Guodong; Liu, Jie; Ding, Lijuan (Frontiers in Earth Science, 2023)
Anti-slide pile is one of the most used measures in landslide control globally. Following its application, various structures have been developed. In this paper, we study the anti-slide pile structure development process and extract two development paths. One path is aimed at improving the applicability. The second path starts from an in-depth study of pile–soil interaction. However, these two paths share single design concept: the anti-slide pile provides direct resistance to maintain landslide stability, that is, the anti-slide pile and the landslide body are thought to be confrontational sides. We here propose developing and utilizing the landslide body in anti-slide pile design. Accordingly, the confrontation relationship between the anti-slide pile and the landslide body can be changed while shifting away from the view that the landslide body is only a hazard. On this basis, we also design a novel structure—arm-stretching-type anti-slide pile. The simulation verification results show that the novel structure works well in realizing the proposed design concept. Compared with the commonly used wholly buried pile, the safety factor of landslide controlled by the novel structure improves by 43.56%. This study promotes the design concept of anti-slide pile developing from the existing slide–resist single mode to the slide–self-stabilize–resist compound mode.